Biomechanical analysis of the isokinetic concentric contraction of knee joints in volleyball players and high jumpers - Xia, L.; Wang, X. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Muscular strength is one of the most important components of physical fitness. It is of great importance to improve muscular strength both for high performance and injury prevention. One of the most common methods to assess muscle strength balance between dominant/non-dominant muscles and antagonist/agonist muscles is isokinetic testing. It has been suggested that bilateral strength differences and the ratio between antagonist/agonist muscles are related to specific sport demands. The purpose of the study was to compare the isokinetic strength of quadriceps and hamstring muscles of volleyball players and high jumpers.